BUDAYA ARAB DAN IDENTITAS SULAWESI SELATAN - Mauliadi Ramli (Universitas Negeri Makassar, 2023)
v ABSTRACTArabic culture has influenced South Sulawesi for centuries and this influence is still evident in local people's lives. This article examines how Arab culture shapes South Sulawesi's identity from the perspective of religion, language, art, and social life. The author uses the library method with analysis from various relevant literature sources. The results of the study show that Arabic culture has become an inseparable part of South Sulawesi's identity and the local community views it as a cultural heritage that must be preserved. We hope that this article can contribute to understanding the relationship between Arab culture and South Sulawesi identity and provide new insights into Indonesian cultural studies. Keywords: Arabic Culture, South Sulawesi, Identity ABSTRACTArabic culture has influenced South Sulawesi for centuries and this influence is still evident in local people's lives. This article examines how Arab culture shapes South Sulawesi's identity from the perspective of religion, language, art, and social life. The author uses the library method with analysis from various relevant literature sources. The results of the study show that Arabic culture has become an inseparable part of South Sulawesi's identity and the local community views it as a cultural heritage that must be preserved. We hope that this article can contribute to understanding the relationship between Arab culture and South Sulawesi identity and provide new insights into Indonesian cultural studies.